AUDIT SISTEM INFORMASI INPUT DATA KENDARAAN BERMOTOR DI UNIT PELAYANAN TEKNIS DAERAH SAMSAT KOTA SERANG MENGGUNAKAN FRAMEWORK COBIT 5 - Batee, Welni Desrinayanti; Auliana, Sigit; Permana, Basuki Rakhim Setya; Aryono, Gagah Dwiki Putra; Masyuri, Umar (CONTEN : Computer and Network Technology, 2024)
This study aims to evaluate the effectiveness and efficiency of the motor vehicle data input information system at UPTD SAMSAT Serang City using the COBIT 5 framework. The methodology used includes observation, interviews, and secondary and primary data collection. The assessment was carried out using the EDM02 (Ensure Continuous Monitoring and Evaluation) and APO12 (Assessing Risk) processes from COBIT 5. The results showed that the current vehicle data input system still faces several challenges, especially in terms of data validation and data duplication prevention. Based on these findings, recommendations are given to improve the data input process to make it more effective and efficient. Implementation of the improvements is expected to improve the quality of data generated and support SAMSAT's overall operations. This research provides practical contributions in the form of specific and measurable recommendations to improve the performance of information systems at UPTD SAMSAT Serang City and provides insight into the application of COBIT 5 in information systems audits.